2010
DOI: 10.2754/avb201079040551
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Fillets of Mirror Crossbreds Common Carp (Cyprinus carpio L.)

Abstract: This paper presents the results of a study dealing with chemical composition of fillets and fatty acid composition (saturated fatty acid: SFA, monounsaturated fatty acid: MUFA, polyunsaturated fatty acid: PUFA) of lipids. Three groups of the mirror hybrid carp in age of three years: M2 × L15 -the Hungarian Szarvas mirror carp (M2) and the Hungarian hybrid mirror strain (L15), M2 × DOR 70 (the Israeli breed -DOR70), M2 × M72 (Northern mirror carp -M72) were compared with: the pure breed M2 and scaly hybrid ROP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…At the same time, a decrease occurs in the percentage of n-3 PUFA (Fajmonová et al 2003; Buchtová et al 2007). According to the research conducted by Buchtová et al (2010) and Ćirković et al (2012), the carp grown on natural food had a high content of both n-6 and n-3 fatty acids. Ćirković et al (2011) observed that PUFA/SFA ratio was the most favourable in the carp fed completed feed mixtures and the least in that fed with maize and wheat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, a decrease occurs in the percentage of n-3 PUFA (Fajmonová et al 2003; Buchtová et al 2007). According to the research conducted by Buchtová et al (2010) and Ćirković et al (2012), the carp grown on natural food had a high content of both n-6 and n-3 fatty acids. Ćirković et al (2011) observed that PUFA/SFA ratio was the most favourable in the carp fed completed feed mixtures and the least in that fed with maize and wheat.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition of fish varies greatly from one species to another and from one individual to another depending on the diet, age, sex, environment and season (Celik et al 2005;Steffens & Wirth 2007;Guler et al 2008;Buchtová et al 2010). Fatty acid composition also varies largely depending on the fish species, on their being wild fish or farm-raised, on the age of fish and on the origin of diets and its composition Yeganeh et al 2012;Ljubojević et al 2013).…”
mentioning
confidence: 99%
“…Many researchers are interested in chemical composition of mirror carp (Buchtová et al 2010;Gümüs 2011;Karaçal et al 2011). Many researchers are interested in chemical composition of mirror carp (Buchtová et al 2010;Gümüs 2011;Karaçal et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The aquaculture fro m local population carp (Ciprinus carpio L.) cultivated in different aquatic systems may differ in terms of their growth, metabolism nutrit ional value, dietary qualit ies and technological properties of fish meat (Atanasov et al, 2009;Buchtová et al, 2010). More research is required to assess the impact of various technological approaches aimed at increasing fish quality (Nikolova, 2013).…”
Section: Introductionmentioning
confidence: 99%